Providing Surround Sound with Loudspeakers: A Synopsis of Current Methods - BLAUERT, Jens; RABENSTEIN, Rudolf (Archives of Acoustics, 2013)
Available methods for room-related sound presentation are introduced and evaluated. A focusis put on the synthesis side rather than on complete transmission systems. Different methods arecompared using common, though quite general criteria. The methods selected for comparison are:INTENSITY STEREOPHONY after Blumlein, vector-base amplitude panning (VBAP), 5.1-SURROUNDand its discrete-channel derivatives, synthesis with spherical harmonics (AMBISONICS, HOA), synthesisbased on the boundary method, namely, wave-field synthesis (WFS), and binaural-cue selection methods(e.g., DIRAC). While VBAP, 5.1-SURROUND and other discrete-channel-based methods show a numberof practical advantages, they do, in the end, not aim at authentic sound-field reproduction. The so-calledholophonic methods that do so, particularly, HOA and WFS, have specific advantages and disadvantageswhich will be discussed. Yet, both methods are under continuous development, and a decision in favorof one of them should be taken from a strictly application-oriented point of view by considering relevantapplication-specific advantages and disadvantages in detail.